Freud's theory and its use in literary and cultural studies : an introduction - Berg, Henk de, 1963- (Studies in German literature, linguistics, and culture., 2003)
"Rarely has a single figure had as much influence on Western thought as Sigmund Freud. His ideas permeate our culture to such a degree that an understanding of them is indispensable. Yet many otherwise well-informed students in the humanities labor under misconceptions or lack of knowledge about Freudian theory. There are countless introductions to Freudian psychoanalysis but, surprisingly, none that combine a genuinely accessible account of Freud's ideas with an introduction to their use in literary and cultural studies, as this book does. It is written specifically for use by advanced undergraduate and graduate students in courses dealing with literary and cultural criticism, yet will also be of interest to the general reader."--Book jacket.